2018
DOI: 10.1016/j.ijnss.2018.06.002
|View full text |Cite|
|
Sign up to set email alerts
|

Family members' perspective of family Resilience's risk factors in taking care of schizophrenia patients

Abstract: Background : Good sibling relationships in adulthood are known to be a protective factor for mental health. The present study examined and compared the relationships of siblings with either a healthy brother or sister or one experiencing schizophrenia. Methods : In the first phase, we ran a statistical comparison of the two sibling groups on the quality of their sibling relationships (warmth, conflict, and rivalry), emotional distress, and self-esteem. In the second phase, we looked at whether the quality of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 29 publications
3
56
0
9
Order By: Relevance
“…These findings suggest that providing care to affected family members may result in physical, emotional, financial and social burdens that can diminish their (family) quality of life. This is supported by studies in other fields [65][66][67][68]. However, in the present study we found that most people receive social and physical support from their families.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 90%
“…These findings suggest that providing care to affected family members may result in physical, emotional, financial and social burdens that can diminish their (family) quality of life. This is supported by studies in other fields [65][66][67][68]. However, in the present study we found that most people receive social and physical support from their families.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 90%
“…Another important implication for both policy and research emanates from the absence of the caregivers' voice in mental health advocacy. The family burden of managing schizophrenia has been widely reported [45,46,80], with families identifying finances and disruption of family functioning [97], confusion and not knowing about schizophrenia [98]. It was evident from our study and fieldwork experience, interviews and talking with relatives of participants and mental health stakeholders, that there was a lack of an advocacy body representing the needs and affairs of family and relatives caring for participants with schizophrenia.…”
Section: Implications For Policy Practice and Researchmentioning
confidence: 82%
“…Our results also showed that the participants in the SZ sample reported more conflict in their sibling relationships than the participants drawn from the general population. The emotional burden, characterized by feelings of fear and impotence on the part of family members, can manifest itself as hostile and critical comments [60]. This hostility from close family and friends, reported in the literature in terms of expressed emotion [61,62], substantially increases patients' risk of relapse [63], and perhaps their suicidality.…”
Section: Conflict In Sibling Relationshipsmentioning
confidence: 99%